Branding and National Identity: The Analysis of “Turkey: Discover The Potential” Campaign - (:unkn) unknown (My University, 2017)
Nation branding has been an important communication strategy forthe governments all around the world in the 21st century. Functioningas a vehicle for conveying messages regarding the nation’s identityto internal and external audiences, nations are imaged and communicatedto the wider audiences as brands. As a regional power withpolitical, historical, cultural and economic significance, Turkey is oneof the countries attempting at nation branding in recent years. Inthis regard, this article analyzes Turkey’s nation branding campaigninitiated in 2015, under the slogan “Turkey: Discover the Potential”.With the analysis of elements constituting brand identity, logo andadvertisements,this article aims to point out the textual and visualways in which Turkey is branded with a particular national identityfor internal and global audiences.

Ulus markalama dünyanın dört bir yanındaki devletlerin 21. yüzyılda kullandıkları önemli bir iletişim stratejisi olmuştur. Bir milletin kimlik ve değerlerine dair mesajların, gerek ülke vatandaşlarına gerekse yabancı izleyicilere aktarılmasını amaçlayan ulus markalama, milletleri bir marka olarak yeniden düzenlemekte ve kitlelere duyurmaktadır. Sahip olduğu siyasi, tarihsel, kültürel ve ekonomik önem nedeniyle bölgesel bir güç olan Türkiye de yakın dönemde ulus markalama uygulayan devletlerden biridir. Bu bağlamda, bu çalışma Türkiye’nin 2015 yılında “Türkiye: Gücünü ve Potansiyelini Keşfet” sloganıyla uygulamaya koyduğu ulus markalama kampanyasını analiz etmektedir. Marka kimliği, logo ve reklamların analiziyle bu çalışma, Türk milletinin belirli bir marka kimliği inşasıyla iç ve dış izleyicilere yönelik markalanma sürecinin metinsel ve görsel pratiklerini incelemeyi hedeflemektedir.
Markalama ve Millî Kimlik: “Türkiye: Gücünü ve Potansiyelini Keşfet” Kampanyası Analizi